2013
DOI: 10.1556/oh.2013.29629
|View full text |Cite
|
Sign up to set email alerts
|

Stage distribution of malignant melanomas in a Hungarian centre

Abstract: Bevezetés: A malignus melanoma túlélése elsősorban a TNM-stádium függvénye, azonban a Nemzeti Rákregiszter a daganatokat stádiumok alapján nem részletezi. Célkitűzés: A szerzők a Semmelweis Egyetem, Bőr-, Nemikórtani és Bőronkológiai Klinikán melanomával kezelt betegek stádiumfelmérését tűzték ki célul. Módszer: A vizsgálat 2004-2009 között diagnosztizált 1160 cutan melanomás betegre (558 férfi és 602 nő, átlagéletkoruk 60,5±16, illetve 57±17 év) terjedt ki. Eredmények: Nagy esetszámú nemzetközi vizsgálatokkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The stage distribution of PAM patients (stage I in 61.7 % and stage IV in 2.9 %) was almost the same as a previous study from our Department, which showed that the majority of the diagnosed melanomas were stage I (60.4 %) and just in 0.4 % of melanomas were detected in stage IV [28].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The stage distribution of PAM patients (stage I in 61.7 % and stage IV in 2.9 %) was almost the same as a previous study from our Department, which showed that the majority of the diagnosed melanomas were stage I (60.4 %) and just in 0.4 % of melanomas were detected in stage IV [28].…”
Section: Discussionsupporting
confidence: 85%
“…The mean age of women at melanoma diagnosis was 32.5 ± 5.6 years (min.-max. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Most PAMs (23/34, 67.6 %) were diagnosed at very early stages (2/34 (5.9 %) in situ melanoma, 21/34 (61.7 %) stage I melanoma).…”
Section: Temporal Relation and Clinical Staging Of Melanoma To Pregnancymentioning
confidence: 99%